Nanoencapsulated rituximab mediates superior cellular immunity against metastatic B-cell lymphoma in a complement competent humanized mouse model. Issue 2 (16th February 2021) - Wen, Jing; Wang, Lan; Ren, Jie; Kranz, Emiko; Chen, Shilin; Wu, Di; Kanazawa, Toshio; Chen, Irvin; Lu, Yunfeng; Kamata, Masakazu
Abstract : Background: Despite the numerous applications of monoclonal antibodies (mAbs) in cancer therapeutics, animal models available to test the therapeutic efficacy of new mAbs are limited. NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice are one of the most highly immunodeficient strains and are universally used as a model for testing cancer-targeting mAbs. However, this strain lacks several factors necessary to fully support antibody-mediated effector functions—including antibody-dependent cellular cytotoxicity, antibody-dependent cellular phagocytosis, and complement-dependent cytotoxicity (CDC)—due to the absence of immune cells as well as a mutation in the Hc gene, which is needed for a functional complement system. Methods: We have developed a humanized mouse model using a novel NSG strain, NOD.Cg −Hc1 Prkdc scid Il2rgtm1Wjl/SzJ (NSG −Hc1 ), which contains the corrected mutation in the Hc gene to support CDC in addition to other mechanisms endowed by humanization. With this model, we reevaluated the anticancer efficacies of nanoencapsulated rituximab after xenograft of the human Burkitt lymphoma cell line 2F7-BR44. Results: As expected, xenografted humanized NSG −Hc1 mice supported superior lymphoma clearance of native rituximab compared with the parental NSG strain. Nanoencapsulated rituximab with CXCL13 conjugation as a targeting ligand for lymphomas further enhanced antilymphoma activity in NSG −Hc1 mice and, more importantly, mediated antilymphoma cellular responses. Conclusions: These results indicate that NSG −Hc1 mice can serve as a feasible model for both studying antitumor treatment using cancer targeting as well as understanding induction mechanisms of antitumor cellular immune response.